Pengaruh Model Pembelajaran Talking Stick Berbantuan Media Question Box Terhadap Hasil Belajar Tema 7 Subtema 1 Siswa Kelas V SDN 066661 Medan Deli T.A 2022/2023 - Sembiring, Esy Putriyani; Perangin-Angin, Laurensia M.; Rangkuti, Irsan; Simanihuruk, Lidia; Rozi, Fahrur (Journal of Student Development Information System (JoSDIS), 2023)
This study aims to determine the effect of applying the Question Box-Assisted Talking Stick learning model to see the learning outcomes of theme 7 sub-theme 1 in class V. This type of research is quantitative research. The research method used is Quasi Experimental with Nonequivalent Control Group Design. The population used was class V-A and V-B of SDN 066661 Medan Deli with a total of 50 students. The sample used was the total sample, namely V-A, 25 students from the experimental class and V-B, namely 25 students from the control class. Data collection techniques used are test and documentation techniques. Based on the results of the study, it was found that there was an influence from the application of the Talking Stick learning model assisted by the Question Box media. This can be seen from the difference in the average score of student learning outcomes in the experimental class was 83.6 and the average value of student learning outcomes in the control class was 79. 6. This is proven by student learning outcomes which can be seen from the difference in the average pretest and posttest scores which have a significant (2-tailed) sig. of 0.000 or p <0.05 in the Paired Sample t Test. Then the acquisition of tcount (-15.007) > ttable (0.404) where ttable with df = 24 at a significance level of 5% with an absolute value of 0.404 then H0 is rejected and Ha is accepted. This shows that there is a significant difference between the Posttest results of the experimental class which was given treatment with the Talking Stick learning model assisted by Question Box media and the control class which used the conventional model.